2021
DOI: 10.3390/ijms22126612
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes on Maternal–Fetal Interface in Placental Abruption—A Systematic Review

Abstract: Placental abruption is the separation of the placenta from the lining of the uterus before childbirth. It is an infrequent perinatal complication with serious after-effects and a marked risk of maternal and fetal mortality. Despite the fact that numerous placental abruption risk factors are known, the pathophysiology of this issue is multifactorial and not entirely clear. The aim of this review was to examine the current state of knowledge concerning the molecular changes on the maternal–fetal interface occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 141 publications
0
5
0
Order By: Relevance
“…Recently immerging data is also demonstrating the link between the in ammatory markers NLR value is higher in preeclampsia patients especially in severe preeclampsia [9]. Molecular Changes on maternal fetal Interface manifested an increased risk of abruption in cases of placental in ammatory lesions, which suggests that the pathophysiologic and etiologic basis for placental abruption is a chronic in ammatory processes [24]. Klement AH Including 11,415 patients described that NLR and PLR values were signi cantly different in the 1 st, 2nd, and 3rd trimesters in a cohort of pregnant women [25],in contrast, Liad Alfandari have demonstrated that predicting values of NLR and PLR were not signi cantly different compare the placental abruption to the control group before 20th weeks of pregnancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently immerging data is also demonstrating the link between the in ammatory markers NLR value is higher in preeclampsia patients especially in severe preeclampsia [9]. Molecular Changes on maternal fetal Interface manifested an increased risk of abruption in cases of placental in ammatory lesions, which suggests that the pathophysiologic and etiologic basis for placental abruption is a chronic in ammatory processes [24]. Klement AH Including 11,415 patients described that NLR and PLR values were signi cantly different in the 1 st, 2nd, and 3rd trimesters in a cohort of pregnant women [25],in contrast, Liad Alfandari have demonstrated that predicting values of NLR and PLR were not signi cantly different compare the placental abruption to the control group before 20th weeks of pregnancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions share similar biological pathways with spontaneous preterm birth, such as disruption of pro-and anti-inflammatory cytokine balance and localized changes to the function of neutrophils, macrophages, T-cells, regulatory T-cells, and Bcells at the maternal-fetal interface. [9][10][11][12] Indeed, both sterile inflammation and infectious inflammation (due to polymicrobial bacterial infection) are major contributors to preterm births. [12][13][14] However, the field lacks a complete understanding of the biological pathways that explain these observations.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Indeed, both sterile inflammation and infectious inflammation (due to polymicrobial bacterial infection) are major contributors to preterm births. [12][13][14] However, the field lacks a complete understanding of the biological pathways that explain these observations. 3 Additionally, treatments including antibiotics, tocolytics, and progesterone supplementation have been implemented with limited success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact etiology of placental abruption—a relatively rare, yet severe, complication of pregnancy with partial or complete placental detachment before the birth of the fetus—is unknown [ 20 ]. A systematic review of the original papers on molecular changes in the maternal–fetal interface coexisting with placental abruption was carried out by Bączkowska et al, 2021 [ 21 ]. Consistently reported chronic noninfectious inflammation and excessive cytotoxic response within the placental tissue may indicate that the disruption of the immunological processes is an important etiological factor in this obstetrical complication.…”
mentioning
confidence: 99%